2004
DOI: 10.1007/s00383-004-1146-2
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-term functional and cosmetic results of the Snodgrass procedure in distal and midpenile hypospadias

Abstract: We have evaluated the long-term functional and cosmetic results of the Snodgrass technique in the treatment of anterior and midpenile hypospadias. A total of 70 patients who presented in the period between 1997 and 2002 underwent the Snodgrass procedure for the treatment of hypospadias. Patients who had been operated on 2 or more years previously were recalled for evaluation. Of the 31 cases identified, 19 (61%) were contacted and came for reevaluation. Genital examination and urinary flow measurements were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Using the nomogram by Mattsson and Spangberg, 10 Malyon et al found that 60% of patients with hypospadias have a Qmax which lies around the 5th centile. 26 Contrary to these findings, Garibay, 28 Gurdal, 29 Kaya 22 and MacMillan 30 et al demonstrated that at mediumterm followup hypospadias surgery produced satisfactory functional results. Gurdal 29 and MacMillan 30 et al found that 95% of patients had a normal Qmax.…”
Section: Discussionmentioning
confidence: 86%
“…Using the nomogram by Mattsson and Spangberg, 10 Malyon et al found that 60% of patients with hypospadias have a Qmax which lies around the 5th centile. 26 Contrary to these findings, Garibay, 28 Gurdal, 29 Kaya 22 and MacMillan 30 et al demonstrated that at mediumterm followup hypospadias surgery produced satisfactory functional results. Gurdal 29 and MacMillan 30 et al found that 95% of patients had a normal Qmax.…”
Section: Discussionmentioning
confidence: 86%
“…Using other nomograms, the results may differ. When evaluating our material with Toguri's nomograms [15], as used by Gürdal et al [16], there was a difference, especially among the young boys. One year postoperatively 18 patients had a flow rate below the 5th percentile using the Miskolc nomograms, compared to only four boys using the Toguri nomograms.…”
Section: Discussionmentioning
confidence: 97%
“…In that study, the authors reported that 7 of the 48 patients had a low flow rate, 6 had meatal stenosis and only 1 had a urethral stricture, and they also concluded that a low flow rate did not specifically indicate urethral stricture. In other retrospective studies, Gurdal et al [20] performed uroflow after TIPU and found that 1 of the 31 patients had meatal stenosis and none had urethral stricture. Marte et al [3] evaluated proximal TIPU with uroflow and found 3 patients with apparent obstruction -all with meatal stenosis.…”
Section: Discussionmentioning
confidence: 99%